Assessment of Biometric Evaluation of Mandible in Tiger (Panthera tigris) - Tiwari, Y.; Pandey, A.; Taluja, J. S.; Vaish, R. (Cutting Edge Research in Biology Vol. 1, 2022)
The present study was proposed to keep on record the gross anatomical features of mandible of tiger (Panthera tigris). It is important to understand that tigers play a vital role in the ecosystem, as they are a predator at the top of the food chain: the apex predator. Tigers (Panthera tigris) have evolved their jaw for predation and deadly bites. They shred their prey's throat with a huge canine, severing the nerves and blood vessels in the process and causing a swift collapse. Gross anatomical study was conducted on mandibles of 5 adult tigers (age more than 8 years) of either sex. It was found that the mandible was the largest and thickest bone of the skull weighing 350.9gm. It forms the lower jaw in tiger. The mandible was formed of 2 halves which were symmetrical to each other and were fused rostrally by symphysis. Each half was consisted of one horizontal rod like part, it was flattened mediolaterally and thicker anteriorly. The other part was vertical, short plate like dorsal border of symphysis was bearing alveoli for teeth. The alveoli of each corner were larger for canine and medial to this 3 small alveoli were present on each side for incisors.Only three cheek teeth were present on each side of the dorsal border of the mandible's horizontal portion, which had three alveoli. Large foramina in the mandible and brain were present. The results of this study show that the presence of three incisor teeth and a more pronounced mandibular angle distinguish the mandible of the tiger from that of the leopard on gross morphological and morphometrical characteristics. . The information obtained in the present study would be useful for identification of bones of tiger and also as an aid in wildlife forensic.